Investigating Hybridization between the Two Sibling Bat Species Myotis myotis and M. blythii from Guano in a Natural Mixed Maternity Colony. - Eve Afonso; Anne-Claude Goydadin; Patrick Giraudoux; Gilles Farny (PLoS ONE, 2017)
Because they can form seasonal mixed-species groups during mating and maternal care, bats are exciting models for studying interspecific hybridization. Myotis myotis and M. blythii are genetically close and morphologically almost identical, but they differ in some aspects of their ecology and life-history traits. When they occur in sympatry, they often form large mixed maternity colonies, in which their relative abundance can vary across time due to a shift in the timing of parturition. For the first time, we used non-invasive genetic methods to assess the hybridization rate and colony composition in a maternity colony of M. myotis and M. blythii located in the French Alps. Bat guano was collected on five sampling dates spread across the roost occupancy period and was analysed for individual genotype. We investigated whether the presence of hybrids followed the pattern of one of the parental species or if it was intermediate. We identified 140 M. myotis, 12 M. blythii and 13 hybrids among 250 samples. Parental species appeared as genetically well-differentiated clusters, with an asymmetrical introgression towards M. blythii. By studying colony parameters (effective size, sex ratio and proportion of the three bat types) across the sampling dates, we found that the abundances of hybrid and M. blythii individuals were positively correlated. Our study provides a promising non-invasive method to study hybridization in bats and raises questions about the taxonomic status of the two Myotis species. We discuss the contribution of this study to the knowledge of hybrid ecology, and we make recommendations for possible future research to better understand the ecology and behaviour of hybrid individuals.